Development of a nomogram for screening of hepatitis B virus-associated hepatocellular carcinoma - Chung, Jung Wha (Oncotarget, 2017)
Current strategy of hepatocellular carcinoma (HCC) surveillance evaluates individual risks of HCC for defining candidates for surveillance, but estimated risks are not utilized for clinical decision-making during actual screening. We sought to determine whether consideration of individual risks improve the performance of ultrasound (US)-based HCC screening in a real-world chronic hepatitis B (CHB) cohort. This single center retrospective cohort study analyzed 27,722 screening US tests from 4,175 consecutive CHB patients. Logistic regression analysis was performed to identify independent parameters predicting presence of HCC. A nomogram was built based on the independent predictors of HCC and compared with US-only screening by receiver operating characteristics analysis. The cost-effectiveness of the nomogram was assessed by decision curve analysis. HCC developed in 222 patients with the incidence of 0.769 per 1000 person-year during the median follow-up of 63 months. Age, sex, presence of cirrhosis, serum alpha-fetoprotein (AFP) levels and positive US test results were independent predictors of HCC presence. A nomogram based on these predictors showed higher C-statistics compared to US-only screening (0.960 vs. 0.731 and 0.935 vs. 0.691 for derivation and validation cohort, respectively; p < 0.001). Decision curve analysis showed higher net benefit of the HCC nomogram-guided screening model compared to US-only screening in the risk threshold range between 0 and 0.3. A nomogram composed of age, sex, presence of cirrhosis, serum AFP levels and US findings better predicted the presence of HCC compared to US-only screening in CHB on surveillance.